2001
DOI: 10.1016/s0039-6028(01)01157-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling sublimation and atomic layer epitaxy in the presence of competing surface reconstructions

Abstract: We present a solid-on-solid model of a binary AB compound, where atoms of type A in the topmost layer interact via anisotropic interactions different from those inside the bulk. Depending on temperature and particle flux, this model displays surface reconstructions similar to those of (001) surfaces of II-VI semiconductors. We show, that our model qualitatively reproduces many of the characteristic features of these materials which have been observed during sublimation and atomic layer epitaxy. We predict some… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This re-arrangement of the surface is observed under step flow sublimation, as demonstrated earlier in Refs. 16,17, and a semi-quantitative agreement with experimental data can be achieved.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This re-arrangement of the surface is observed under step flow sublimation, as demonstrated earlier in Refs. 16,17, and a semi-quantitative agreement with experimental data can be achieved.…”
Section: Discussionsupporting
confidence: 65%
“…Chemical bonds and the influence of the underlying crystal were accounted for by effective pairwise anisotropic interactions. Sublimation and ALE growth have been studied in the framework of a simple cubic model, 17 which accounted only for the most essential features of CdTe. The correct zinc-blende lattice was first considered in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…At the temperature of the c(2 × 2) Cd -(2 × 1) Cd transition, sublimation plays an important role. However, in a previous publication [23] we have shown that the basic features of a simplified version of our model which neglects Te dimerization [12] are preserved under the conditions of step flow sublimation. This is the dominant sublimation mechanism for CdTe (001) [24].…”
Section: Comparison With Experimental Resultsmentioning
confidence: 75%
“…Biehl et al introduced the anisotropic two‐dimensional lattice gas model for investigations of the metal‐terminated II–VI (001) semiconductor surfaces 17–20. This model reproduces many of the characteristic features of these materials.…”
Section: Introductionmentioning
confidence: 99%